MAQASID SYARI’AH DAN PENGEMBANGAN HUKUM (Analisis Terhadap Beberapa Dalil Hukum) - Rauf, Aris (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2014)
This paper studies regarding one aspect of the discussion about the science of usul Fiqhi Maqasid Shariah law and development. The issue is how maqasid role in the development of Shariah law. In the discussion of its principles Fiqhi, one method of extracting law is Shariah maqasid approach. Through Shariah maqasid verses and hadiths law quantitatively very limited amount can be developed to address the problems that arise. Legal development is done by using the method of determination of the law such as qiyas, maslahah mursalah and istihsan. Methods of determination is through maqasid Shariah law.